Vibroacoustic monitoring of bearing points failures in the driving system of the mining main ventilation fans - T. ZAKRZEWSKI (Archives of Acoustics)
Bearing points constitute the integral part of present-day machinery. They often limit in the service life of machines. As there is no access to them in the course of operation, diagnostic methods which can be applied without dismantling the machine, and particularly vibroacoustic methods based on the fact that there is a dependence between failure-free operation and the vibroacoustic condition of bearings become more and more essential. The evaluation of the technical condition of rolling and slide bearings, based on measures of a vibratory signal, made on the basis of amplitude values of discrete components occurring in the spectra of the recorded vibratory signals, has; been the subject of diagnostic examinations. The study also covered the rolling bearings and slide bearings supporting the main shaft of the mine fans driving system of WPK type, designed for main ventilation in normal conditions of their operation. It is worth noting that considerably less work has been devoted to the elaboration of methods of vibroacoustic diagnosis for slide bearings than the methods for rolling bearings although slide bearings also constitute weak points in a number of machines. Many reasons account for such a situation, above all the fact that a slide bearing is characterized by low vibroactivity in comparison with that of other points of machines. This means that weak vibroacoustic signals are generated in slide bearings and it is sometimes difficult to isolate them from the noise present, in particular, in sophisticated machinery. The purpose of the examinations carried out on separated bearing points was to evaluate the range of sensitivity of the introduced, relatively simple, estimates of the recorded vibratory signals, to changes of the degree of wear in the conditions of constant loading and increasing period of operation. The obtained results, and the analysis of these results, served as the basis for elaborating the criteria for the evaluation of the technical state of bearing points. Here, such diagnosis estimates were selected that their values determined at the moment of checking, allowed to draw conclusions on the functional characteristics of the bearing points.